Analysis for a 3D structure of a protein through molecular modelling and simulation - Sharma, Nitin; Chauhan, Pallavi; Shakya, Madhvi (Fırat Evirgen, 2025)
One of the most exciting and challenging topics in biophysics and computational biology is the prediction of a protein’s 3D structure from its amino acid sequence, due to its functional relevance. In this study, molecular modeling and simulation approaches are employed to predict the 3D structure of a protein. Valuable information for wet lab experiments-such as B-factor analysis, energy minimization states, and the determination of Phi $(\phi)$/Psi$(\psi)$ angles-has been obtained through this research. A case study involving the human prion protein 1HOL is presented to demonstrate the methodology, with a structural comparison made between the 1HOL-modeled protein and the protein structure determined by Nuclear Magnetic Resonance (NMR) spectroscopy. The molecular model of 1HOL was constructed using the homology modeling software MODELLER, and molecular dynamics simulations were performed using the GROMACS software. The strong positive correlation between the RMSD of the modeled protein and that of the NMR-determined protein indicates that the predicted structure closely approximates the experimentally determined NMR structure.
Keywords: Sequence Analysis; Sekans Analizi; Molecular Docking; Moleküler Yerleştirme; Biological Mathematics; Biyolojik Matematik